Persistence of bactericidal antibodies following primary and booster MenACWY-TT vaccination of toddlers: A review of clinical studies. Issue 27 (2nd June 2020) - Webber, Chris; Peyrani, Paula; Balmer, Paul; Serra, Lidia
Abstract: The long-term persistence of antibody responses following primary vaccination with quadrivalent conjugate vaccines targeting meningococcal serogroups A, C, W, and Y (MenACWY) and the duration of protection following a booster dose have not been fully elucidated, particularly in children who received primary dosing as toddlers. This review summarizes the findings of one phase 3 and three phase 2 open-label, randomized clinical studies that assessed the long-term antibody persistence of MenACWY conjugated to tetanus toxoid as a carrier protein (MenACWY-TT) in toddlers. Following primary vaccination, antibody responses persisted for approximately 2–3 years and then decreased up to 5 years after vaccination. Geometric mean titers remained elevated for all serogroups up to 5 years after primary vaccination. In children who received a booster dose of MenACWY-TT at 4–5 years after primary dosing as toddlers, antibody responses were documented in >99% of subjects across all serogroups, with minimal decreases in antibody persistence from 2–6 years after booster vaccination. The persistence of meningococcal serogroup C (MenC) antibody responses was similar between MenACWY-TT and MenC vaccine recipients after primary and booster dosing. Together, these findings indicate that antibody responses to primary MenACWY-TT vaccination persist for 2–3 years. Additionally, these findings indicate that in subjects who receive primary MenACWY-TT vaccination as toddlers, the antibody response to booster MenACWY-TT vaccination lasts for up to 6 years and suggest that immune memory is afforded at least into early adolescence, which is an age group at increased risk of invasive meningococcal disease.